2006
DOI: 10.1093/her/cyh069
|View full text |Cite
|
Sign up to set email alerts
|

Post-partum intention to resume smoking

Abstract: Little is known about the motivational background of smoking after a period of nicotine abstinence during pregnancy. The study examines the intention to resume smoking (IRS) in the post-partum period and its predictive value for smoking within 12 months post-partum. In a sample of 301 women recruited from obstetric wards who reported having stopped smoking during pregnancy, data on IRS, sociodemographic variables, recent smoking behaviour and smoking in the social network were collected. Smoking status was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 20 publications
(22 reference statements)
2
18
0
2
Order By: Relevance
“…Elevated stress during the post-partum period (26), living with a smoker (25), and intention to resume smoking (34) have all been identified as predictors of post-partum smoking relapse. Our results also support previous findings regarding key factors that contribute to postpartum smoking abstinence, including breastfeeding (35), social support (36), confidence in staying quit (37), and using effective coping strategies (17).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated stress during the post-partum period (26), living with a smoker (25), and intention to resume smoking (34) have all been identified as predictors of post-partum smoking relapse. Our results also support previous findings regarding key factors that contribute to postpartum smoking abstinence, including breastfeeding (35), social support (36), confidence in staying quit (37), and using effective coping strategies (17).…”
Section: Discussionmentioning
confidence: 99%
“…First, compared to others who quit smoking, pregnant women are more likely to be motivated by extrinsic factors (e.g., health of fetus, social pressure, nausea) to suspend their smoking during their pregnancy, rather than attempting to quit permanently (Curry et al, 2001, Roske et al, 2006Stotts et al, 2000). Women who intend to resume smoking after giving birth presumably are less likely to seek help for maintaining their tobacco abstinence (although one-third of our reactive sample reported that they did not plan to "quit for good").…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the motivation to remain abstinent differs among general population quitters and pregnant ex-smokers (Stotts et al, 1996(Stotts et al, , 2000. Clinical experience indicates that smokers in general tend to quit with the goal of continued abstinence, yet many pregnant women who quit smoking are motivated primarily by concerns about the health of the fetus, and therefore plan to abstain only during their pregnancy (Curry et al, 2001;Roske et al, 2006). Women also face unique stressors after they give birth, such as: identity confusion during the transition between pregnancy and postpartum, the reintroduction of smoking cues (e.g., spousal smoking) that were avoided during pregnancy, and the increased stress of caring for a new baby (Quinn et al, 2006).…”
Section: Overview Of Clinical Trialmentioning
confidence: 99%
“…[23,38] Unfortunately, most spontaneous quitters return to smoking during postpartum. [16,23,26,41] The majority resume smoking within six months, [10,25] and this increases to as much as 80% within one year after delivery. [11] The rate of smoking relapse for low-income women is higher than all pregnant women.…”
Section: Discussionmentioning
confidence: 99%